Effect of tool centreline deviation on the mechanical properties of friction stir welded DH36 steel. (January 2015) - Tingey, Christopher; Galloway, Alexander; Toumpis, Athanasios; Cater, Stephen
Highlights: FSW of DH36 was tolerant to a centreline defect induced by tool deviation. High strength welds up to 2.5 mm centreline tool deviation with ductile PM fracture. Critical tolerance to centreline tool deviation at 4 mm with ductile weld metal fracture. Brittle fracture above 4 mm deviation led to significant reduction in yield strength. Abstract: Friction stir welding of steel has gone through recent tool and optimisation developments allowing the process to be considered as a technically superior alternative to fusion welding. This study expanded the scientific foundation of friction stir welding of DH36 steel to analyse the effect on weld quality when the rotating tool increasingly deviates away from the weld centreline. A centreline defect was deliberately but gradually introduced along the length of the weld seam. The tolerance to tool deviation towards both the advancing side and the retreating side of the weld was measured in terms of the transverse yield strength. Three discrete fracture modes were observed in transverse tensile specimen. Up to a tool deviation of 2.5 mm, ductile fracture in the parent material was observed and there was not a significant reduction in the yield strength of the weldment. The critical tool deviation occurred at 4 mm, where transverse tensile specimens fractured in a high strength ductile mode in the weld metal. Brittle behaviour in specimens above the 4 mm tolerance level resulted in a significant decrease in the transverse yield strength. Fracture within the weld metal was directed along the boundary between the heat-affected zone and thermo-mechanically affected zone, attributable to an abrupt change in the grain size and complexity of the two weld zones at this boundary. Friction stir welding of DH36 was found to be a tolerant joining process to the centreline deviation of the rotating tool.